Petroleum Science - Xiao, Lizhi
Petroleum Science is the only English journal in China on petroleum science and technology that is intended for professionals engaged in petroleum science research and technical applications all over the world, as well as the managerial personnel of oil companies. It covers petroleum geology, petroleum geophysics, petroleum engineering, petrochemistry & chemical engineering, petroleum mechanics, and economic management. It aims to introduce the latest results in oil industry research in China, promote cooperation in petroleum science research between China and the rest of the world, and build a bridge for scientific communication between China and the world.